Environmental systems analysis and management : proceedings of the IFIP WG 7.1 Working Conference on Environmental Systems Analysis and Management, Rome, Italy, 28-30 September 1981 - IFIP WG 7.1 Working Conference on Environmental Systems Analysis and Management (1981 : Rome, Italy); Rinaldi, S. (Sergio), 1940-; IFIP WG 7.1 (Amsterdam ; New York : North-Holland Pub. Co. ; New York, N.Y. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1982)
Includes bibliographical references.